2017
DOI: 10.1186/s12866-017-1065-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis IolQ (DegA) is a transcriptional repressor of iolX encoding NAD+-dependent scyllo-inositol dehydrogenase

Abstract: Background Bacillus subtilis is able to utilize at least three inositol stereoisomers as carbon sources, myo-, scyllo-, and D-chiro-inositol (MI, SI, and DCI, respectively). NAD+-dependent SI dehydrogenase responsible for SI catabolism is encoded by iolX. Even in the absence of functional iolX, the presence of SI or MI in the growth medium was found to induce the transcription of iolX through an unknown mechanism.ResultsImmediately upstream of iolX, there is an operon that encodes two genes, yisR and iolQ (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 30 publications
(57 reference statements)
0
23
0
Order By: Relevance
“…There is extensive research on the biochemical pathway and the regulation of bacterial inositol catabolism in Bacillus subtilis. It has been reported that B. subtilis possesses a complete set of iol genes required for its inositol catabolism; including the iolABCDEFGHIJ operon, the iolRS operon, iolQ, iolT, iolU, iolW, and iolX [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive research on the biochemical pathway and the regulation of bacterial inositol catabolism in Bacillus subtilis. It has been reported that B. subtilis possesses a complete set of iol genes required for its inositol catabolism; including the iolABCDEFGHIJ operon, the iolRS operon, iolQ, iolT, iolU, iolW, and iolX [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a recent study demonstrated that in B. subtilis, an additional repressor encoded by iolQ that belongs to the LacI family regulates iolX, encoding an NAD + -dependent scyllo-inositol dehydrogenase [3], although the mechanisms underlying the regulation of iolU and iolW, either of which encodes an NADP + -dependent scyllo-inositol dehydrogenase [5,6], have not been elucidated as they appeared to be almost constitutive. Genetic evidence suggests that scyllo-inositol and myo-inositol could be the intracellular inducers for IolQ; however, both failed to antagonize its DNA binding activity in vitro [3].…”
Section: Introductionmentioning
confidence: 99%
“…scyllo-Inosose is further degraded, enabling it to enter glycolysis and the citric acid cycle following successive reactions catalyzed by the enzymes IolE, IolD, IolB, IolC, IolJ, and IolA. In addition, both IolF and IolT function in transporting inositol into the cell, while IolR and IolQ act as repressors regulating transcription of the iol genes [10][11][12][13][14] . An additional inositol dehydrogenase, IolW, is a key enzyme that enables B. subtilis to produce scyllo-inositol by specifically reducing scyllo-inosose into scyllo-inositol, coupled with the oxidation of NADPH ( Fig.…”
mentioning
confidence: 99%
“…In this case, iolG, iolW, and iolT were simultaneously overexpressed in a strain that lacked all of the other iol genes. In addition, a heterologous nicotinamide nucleotide transhydrogenase capable of regenerating NADPH was introduced, since IolW requires NADPH to reduce scyllo-inosose into scyllo-inositol 14 . The bioconversion is efficient enough to enable a high productivity, but the scylloinositol produced can never be cheaper than the starting material, myo-inositol.…”
mentioning
confidence: 99%
See 1 more Smart Citation